Wind Turbines, Shadow Flicker, and Real Estate Values - Carsten Andersen; Timo Hener (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze the effect of wind turbines on the prices of houses in their proximity. Utilizing the universe of Danish house transactions since 1992 and data on all turbines ever established in Denmark, we are able to control for individual house fixed effects. We distinguish between effects of proximity and shadow flicker from rotor blades partly covering the sun. Our results suggest that nearby turbines have a significant adverse impact on house prices, and this impact is notably more pronounced for taller turbines. Furthermore, homes affected by shadow flicker experience an additional decrease in value comparable to the effect of the tallest turbines. Our findings suggest a nuanced view regarding the local externalities of wind turbines that heavily depend on size and relative location.
Keywords: R31; P18; Q42; 330; wind turbines; house prices; shadow flicker